Sudan Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2016)
The assessment of accounting and auditing (A&A) practices in Sudan is part of the joint initiative of the World Bank and the International Monetary Fund (IMF) to prepare Reports on the Observance of Standards and Codes (ROSC). The ROSC A&A assessment focuses on strengths and weaknesses of the corporate accounting and auditing environment that influence the quality of corporate financial reporting and involves a review of both mandatory requirements and actual practices. It uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on recent global experiences and good practice in the field of corporate financial reporting and auditing. This assessment used a diagnostic template developed by the World Bank to facilitate collection of information, which was complemented by findings of a due diligence exercise based on meetings with key stakeholders conducted by World Bank staff. The assessment was carried out ensuring participation from the in-country major stakeholders such as regulators of corporate entities, banks and similar financial institutions, professional accountants, bankers and investment analysts, preparers of financial statements, auditors, academics, and representatives from the leading trade bodies. The main purpose of this ROSC A&A assessment is to assist the Government of Sudan in strengthening the private sector's accounting and auditing practices, along with enhancing financial transparency in the corporate sector.